Total Elbow Arthroplasty as a Viable Reconstruction Option for Proximal Ulna Giant Cell Tumor: Case Report - Mujaddid Idulhaq; Muhammad Haris Wibowo (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Giant cell tumor (GCT) of bone is a relatively common primary bone tumor, typically benign but known for local aggressiveness and potential for recurrence. It commonly affects the epiphyseal regions of long bones, particularly around the knee. Occurrence in the proximal ulna is rare, accounting for less than 1% of skeletal tumors, posing significant treatment challenges due to the complex elbow anatomy. Treatment aims for complete tumor removal, preservation of function, and prevention of recurrence, with options ranging from curettage to wide resection. Reconstruction after resection, especially involving the joint, is complex. Case presentation: We report the case of a 39-year-old female presenting with a painful swelling in her right elbow three months after a fall. Clinical examination revealed swelling, tenderness, and limited range of motion. Radiographs and MRI showed an expansile lytic lesion in the proximal ulna, suggestive of GCT. The patient underwent wide resection of the tumor followed by reconstruction using total elbow arthroplasty (TEA). Histopathology confirmed the diagnosis of GCT. Conclusion: At 8-month follow-up, the patient demonstrated excellent functional recovery with a range of motion from 0° extension to 150° flexion, a DASH score of 6.7, and an MSTS score of 26, with no signs of local recurrence. This case illustrates that wide resection combined with TEA is a viable and effective treatment strategy for GCT of the proximal ulna, offering good functional outcomes and local tumor control.